An Interhospital, Interdisciplinary Needs Assessment of Palliative Care in a Community Critical Care Context. Issue 4 (December 2015) - Sarti, Aimee J.; Bourbonnais, Frances Fothergill; Landriault, Angèle; Sutherland, Stephanie; Cardinal, Pierre
Aim: There is a paucity of data on the provision of palliative care in the critical care settings of smaller community hospitals. This study aimed to identify the gaps that affect the provision of palliative care in a community critical care setting. Setting: The study was set in a 10-bed, open intensive care unit and emergency department at a community hospital. Methods: Mixed methods were used. Quantitative data included those drawn from databases and surveys; qualitative data included those collected from interviews, focus groups, and onsite walk-throughs and were analyzed with inductive coding techniques. Results: Gaps were identified in palliative care, goals of care and end-of-life discussions, and resources. Community hospital healthcare professionals did not fully appreciate their essential contribution to the provision of palliative care in the intensive care unit. In addition, there was a lack of expertise, and a lack of interest in gaining expertise, in palliative/end-of-life care. Conclusion: Interrelated needs in a complex interprofessional, interhospital context were captured. Further studies are required to obtain data on palliative practice in the care of critically ill patients in various community hospital contexts.